The Impact of Seropositivity on Systemic Bone Loss in Rheumatoid Arthritis—A 3-Year Interim Analysis of a Longitudinal Observational Cohort Study - Yu, Shan-Fu; Chen, Jia-Feng; Chen, Ying-Chou; Wang, Yu-Wei; Hsu, Chung-Yuan; Lai, Han-Ming; He, Hsiao-Ru; Ko, Chi-Hua; Chiu, Wen-Chan; Cheng, Tien-Tsai (Frontiers in Medicine, 2022)
Objective To explore the impact of seropositivity on systemic bone loss in rheumatoid arthritis (RA). Methods We conducted an interim analysis of the RA registry. Patients were examined with dual-energy X-ray absorptiometry at baseline and again 3 years later. Participants were grouped into seropositive (SPRA) and seronegative (SNRA) based on the presence or absence of rheumatoid factor (RF) and/or anti-cyclic citrullinated peptide antibodies (ACPA). After matching (1:2) for age and sex, SNRA and SPRA patients were divided into groups A and B. Each matched group (A or B) was further subdivided according to the number of antibodies present (0, group I; 1, group II; 2, group III). Multiple ordinary least squares regression was used with the dependent variables to develop a model to predict bone mineral density (BMD) change. Results A total of 477 participants who completed a 3-year observation period were included. After matching, 312 participants were enrolled (group A, 104; group B, 208). Three years later, group B had significant BMD reduction in the femoral neck (FN) (p < 0.001), total hip (TH) (p = 0.001), and first through fourth lumbar vertebrae (L1–4) (p = 0.006), while group A had bone loss only at FN (p = 0.002). Groups I, II, and III included 104, 52, and 156 participants, respectively. Compared to baseline, BMD decreased significantly at FN (p = 0.002) in group I, FN (p < 0.001) in group II, and FN (p < 0.001), TH (p = 0.002), and L1–4 (p = 0.016) in group III. In terms of regression-adjusted percent change in BMD, more significantly negative changes were found at all measured sites in group B (p < 0.001, all) and at TH and L1–4 within groups I-III (p for trend < 0.001 and < 0.001, respectively). Regardless of antibodies, anti-osteoporotic therapy can preserve bone density in RA patients. Conclusion After 3 years, SPRA patients lost more bone density than SNRA patients. More attention should be paid to SPRA patients, especially those with double-positive antibodies, including a vigorous evaluation of BMD and fracture risk. Anti-osteoporotic therapy can prevent BMD loss irrespective of autoantibodies.